the effects of the III Africa-Spain Plan through the structural gravity model in partial equilibrium - (:unkn) unknown (My University, 2022)
The adoption of the III Africa-Spain Strategic Plan: Challenge and Opportunity in March 2019 made the African continent one of the new priorities of Spanish foreign policy. Thanks to its new cooperation program, called "Focus Africa 2023", the Iberian kingdom intends to become in ten years a leading partner for the continent. The strategic objectives assigned to this plan are: Peace and security; sustainable development, inclusive and resilient economic growth; Institutional Aspects; and orderly, safe and regular mobility. To do this, taking into account the essential role of international trade in the economic and social development of a nation, it seemed appropriate to us to study, on the basis of data on international trade and Spain's actions in Africa, the effects of the III Africa-Spain Plan through the structural gravity model in partial equilibrium. To achieve this, we have developed a first structural gravity model in partial equilibrium by measuring the impact of Spain's actions in Africa on the bilateral trade flow of flagship and priority countries. The results of this empirical study show that there is: a positive relationship between the influence of the Spanish language, the presence of Spanish companies in Africa, the institutional presence and the bilateral trade flow and a negative relationship between the bilateral distance, conflict resolution and migration issues and trade flows. In order to identify the impact transmission channels of the flagship countries (Nigeria, Ethiopia, South Africa) in their respective RECs and moreover in all of sub-Saharan Africa, we have developed a second structural gravity model in partial equilibrium in integrating the flagship countries only and eight countries of Sub- Saharan Africa chosen according to their demographic and economic size. The results of the estimation of this model show that the variables contiguity, belonging to the same REC and trade flows have a positi
Keywords: African Research